Veclaicenes pagasta pašvaldības budžeta izpilde un analīze - Klaipa, Inuta (Latvijas Universitāte, 2008)
Bakalaura darba tēma ir „Veclaicenes pagasta pašvaldības budžeta izpilde un analīze”.Bakalaura darba mērķis ir uz pieejamās literatūras pamata un uz Veclaicenes pagasta pašvaldības datu analīzes pamata izanalizēt Veclaicenes pagasta pašvaldības budžeta izpildi un izstrādāt priekšlikumus budžeta izpildes kontroles sistēmas uzlabošanai.Darbā ir izpētīts likumos un normatīvajos aktos pašvaldību budžetu vispārējais raksturojumus, izpētīti un izanalizēti pašvaldību ieņēmumi un to avoti, sniegts Veclaicenes pagasta raksturojums, izpētīts īpaši atbalstāmās teritorijas statuss Veclaicenes pagastā, izanalizēta Veclaicenes pagasta pašvaldības ieņēmumu dinamika, izanalizēti Veclaicenes pagasta pašvaldības izdevumi un aplūkotas Veclaicenes pagasta pašvaldības attīstības iespējas. Darba nobeigumā apkopoti secinājumi un izvirzīti priekšlikumi.Darbs ir uzrakstīts latviešu valodā. Satur 65 lapas, 9 tabulas un 19 attēlus.Atslēgvārdi: pašvaldība, budžets, izpilde, analīze.

The theme of the bachelor work is „ Rural municipality Veclaicene self-government budgetary implementation and analysis”.The aim of the bachelor work is on foundation of the accessible literature and on rural municipality Veclaicene self-government data analysis foundation to analyze rural municipality Veclaicene self-government budgetary implementation and to produce suggestions budgetary implementation control system improves. In the work are explored in laws and in the normative acts universal descriptions of self-governments budget, are explored and analyzed the revenue resources of self-governments and their sources, is given the description of rural municipality Veclaicene, is explored status of the Specially support territory in the rural municipality Veclaicene, is analyzed the dynamics of the rural municipality Veclaicene self-government profits, are analyzed the rural municipality Veclaicene self-government charges and are examined rural municipality Veclaicene self-government development possibilities. In completion of the work are summarized conclusions and worked out suggestions.The bachelor work is written in Latvian language. Contain 65 pages, 9 tables and 19 images.Keywords: self-government, budget, implementation, analysis.
Rural municipality Veclaicene self-government budgetary implementation and analysis
Keywords: Ekonomika